ASPEK ASPEK KEMANUSIAAN DALAM TERORISME BERDASARKAN KAJIAN FIKIH - Afifi Fauzi Abbas (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Human right is the basic right possesed by all human beings. This right does not need to be given, purchased or inherited. Human right is automatically part of human, and human right is also applied to all mankind whoever the person, and does not rely on race, ethnicity or religion and age considerations. Humanitarian issues faced by Muslims in Indonesia today is the treatment of the country against terrorism suspects in raids in several cases considered terrorism cases in Indonesia starting from the Bali bombings, Bom Sarinah and several other terrorism cases. Discuss aspects of the humanitarian aspect of terrorism is becoming a necessity, especially when viewed from the perspective of jurisprudence. In Islamic Fiqh, autopsy (forensic) can be done, and the results serve as evidence that the rules of evidence in Islam to be entered into evidence